På jagt efter guldhornenes findested - Thorsen, Sven (Kuml, 2017)
Hunting for the find spots for the golden horns of Gallehus It is common knowledge that the golden horns were found at Gallehus in 1639 and 1734 and, consequently, so early that information on the find spots and finds circumstances is extremely sparse. In 1855, C.C. Rafn reached the conclusion that the horns were discovered in an undeveloped common area in the town (fig. 2), while in 1908, P. Lauridsen believed he had established the precise find spots, which were then marked with commemorative stones (figs. 3 and 4). With the discovery in 1951 of a report from 1734, it became clear that Lauridsen’s locations were incorrect and that the two finds spots are unlikely to have been more than 7 m apart, i.e. significantly less than the distance he concluded (fig. 1). This prompted Professor P.V. Glob to launch an investigation of the area in 1952, aimed at finding possible evidence that could explain these depositions. Glob continued his investigations in 1964, 1969 and 1971-72 (fig. 5). But he never managed to write a concluding report, and this article is an attempt to summarise his findings. The most important of these was the discovery of numerous pits, most of which were not very deep and had a very flat base. Many of them had apparently stood open for a shorter or longer period and they were therefore interpreted as clay pits (figs. 6-8). In 1969, some of these pits were found in an area corresponding to the find spot for one of the golden horns as specified in the 1734 source. Glob therefore believed he had found the actual find spot (figs. 10 and 12). The investigation in 1972 showed that these clay pits lay in the northeastern part of a larger more or less coherent complex of clay pits (fig. 7). Secure dating of these was not possible, but the fact that a house was built in 1832 over the southwesternmost corner of the complex testifies to a considerable age. Sven Thorsen Nykøbing Falster